2011
DOI: 10.1037/a0022179
|View full text |Cite
|
Sign up to set email alerts
|

Gender and racial differences in treatment process and outcome among participants in the adolescent community reinforcement approach.

Abstract: Increasingly, evidence-based treatments are being implemented by community treatment providers, and it is important to understand whether they can be implemented with similar quality and equivalent effectiveness across gender and racial groups. This study examined whether initiation, engagement, dosage, treatment satisfaction, or outcomes for adolescents who received the Adolescent Community Reinforcement Approach (A-CRA) in a large implementation effort were equivalent by gender or racial group. Analyses of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 65 publications
(79 reference statements)
4
38
3
2
Order By: Relevance
“…This lack of ethnic differences in treatment outcome is similar to the findings of Rounds-Bryant and Staab (2001) from the DATOS-A project and those of Strada et al (2006) in their review of ASA treatment studies. Results are also consistent with a recent multisite implementation study by Godley, Hedges, and Hunter (2011), which found that White, African American, and Latino youth had equivalent initiation, engagement, and treatment outcomes following an evidence-based outpatient intervention. Although we cannot disregard the possibility that differential completion of the posttreatment assessment contributes to these findings (discussed further below), our results are bolstered by the large sample size, as well as the consistency with prior investigations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This lack of ethnic differences in treatment outcome is similar to the findings of Rounds-Bryant and Staab (2001) from the DATOS-A project and those of Strada et al (2006) in their review of ASA treatment studies. Results are also consistent with a recent multisite implementation study by Godley, Hedges, and Hunter (2011), which found that White, African American, and Latino youth had equivalent initiation, engagement, and treatment outcomes following an evidence-based outpatient intervention. Although we cannot disregard the possibility that differential completion of the posttreatment assessment contributes to these findings (discussed further below), our results are bolstered by the large sample size, as well as the consistency with prior investigations.…”
Section: Discussionsupporting
confidence: 87%
“…Third, among the variables not included in the EAT database was socioeconomic status (SES), which is often related to ethnicity and therefore may contribute to the observed effects of ethnic status on substance use. Moreover, this analysis intentionally focused on four putative covariates and did not consider other variables that might be associated with ethnicity, such as family composition, criminal justice involvement, level of acculturation, country of origin, and foreign-versus American-born status (Godley et al, 2011;Wallace et al, 2002Wallace et al, , 2003. Given the lack of ethnic effects on posttreatment outcome, confounding effects of SES and other covariates are somewhat less of a concern in this study.…”
Section: Limitationsmentioning
confidence: 99%
“…A-CRA provides significantly more individual CBT sessions with the adolescent-alone compared to other family-based interventions and has been successfully used with homeless and minority youth [22, 23]. …”
Section: Treatmentmentioning
confidence: 99%
“…Importantly, the effectiveness of A-CRA has been supported in randomized clinical trials (Dennis et al, 2004; Godley, Godley, Dennis, Funk, & Passetti, 2007; Slesnick et al, 2007). Moreover, A-CRA has been shown to have relatively high and equivalent rates of treatment engagement, retention, satisfaction, and substance use recovery outcomes across gender and racial groups (Godley, Hedges, & Hunter, 2011). …”
Section: Introductionmentioning
confidence: 99%